2013
DOI: 10.1063/1.4802746
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-enhanced optical detection of carbon nanotube Brownian motion

Abstract: Optical cavities with small mode volume are well-suited to detect the vibration of sub-wavelength sized objects. Here we employ a fiber-based, high-finesse optical microcavity to detect the Brownian motion of a freely suspended carbon nanotube at room temperature under vacuum. The optical detection resolves deflections of the oscillating tube down to 50pm/Hz^1/2. A full vibrational spectrum of the carbon nanotube is obtained and confirmed by characterization of the same device in a scanning electron microscope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…For example, it was shown that a fiberbased optical microcavity can resolve the thermal motion of carbon nanotubes [11]. Another successful sensing scheme consists in introducing nanomechanical resonators in the near field of optical whispering-gallery-mode resonators.…”
Section: Laser Interferometry and Spectroscopymentioning
confidence: 99%
“…For example, it was shown that a fiberbased optical microcavity can resolve the thermal motion of carbon nanotubes [11]. Another successful sensing scheme consists in introducing nanomechanical resonators in the near field of optical whispering-gallery-mode resonators.…”
Section: Laser Interferometry and Spectroscopymentioning
confidence: 99%
“…5.5a is formed between the end facets of two glass fibers acting as cavity mirrors. These micro cavities are employed in several optomechanics experiments [43,[52][53][54]. The following description refers to the specific setup employed in Refs.…”
Section: Fiber-based Fabry-perot Cavitymentioning
confidence: 99%
“…The following description refers to the specific setup employed in Refs. [43,52,53]. In order to optimize both the optical cavity mode as well as the detected cavity transmission T , the input fiber consists of a single mode fiber whereas the output fiber is a multi mode fiber with a larger core.…”
Section: Fiber-based Fabry-perot Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The high-bandwidth readout allows measuring with a large Dx, outside of the mechanical bandwidth. Undriven motion such as thermal motion, 22 zero-point motion, and self-sustained oscillation through single-electron tunneling 3,23 can now be investigated because the mechanical motion can be probed without driving it. Finally, mass sensing experiments 1 can be performed with significantly faster time resolution, opening up the possibility of probing phenomena such as the diffusion of adsorbates on the mechanical resonator.…”
Section: -2mentioning
confidence: 99%